Effects of Organizing Mathematics Learning Activities Using Lesh’s Translation Model and Contextual Teaching and Learning on Mathematical Concept of Lower Secondary Students - Chaimongkhon, Suthita; Nenthien, Sansanee (An Online Journal of Education, 2024)
The purposes of this research were: 1) to compare the mathematical concept of lower secondary school students after learning using Lesh’s translation model and contextual teaching and learning to the 60 percent criteria, and 2) to study the development of the mathematical concept of students through learning using Lesh’s translation model and contextual teaching and learning. The sample for this study consisted of 44 ninth-grade students under the Samut Sakhon Samut Songkhram Secondary Educational Service Area Office. The research instruments consisted of lesson plans, a mathematical concept test, and mathematical concept worksheets. The data were analyzed using arithmetic mean, standard deviation, percentage, t-test, and content analysis. The results of the research revealed that: 1) the students’ mathematical concepts after learning using Lesh’s translation model and contextual teaching and learning had a score of 53.27 percent, which was not higher than the 60 percent criteria, and 2) students’ mathematical concepts after learning using Lesh’s translation model and contextual teaching and learning improved, specifically in terms of explaining characteristics, understanding meaning, and relating mathematical representations of mathematical concepts, and explaining and using formulas, rules, and mathematical procedures.